Implementation of Student Dance Self-Development at SMP Negeri 7 Padang - Anjelina Utari; Marzam (Universitas Negeri Padang, 2024)
The purpose of this study is to learn more about and describe how dance self-development is being implemented at SMP Negeri 7 Padang. It uses a descriptive method with a qualitative research approach. The researcher serves as the main data collecting tool, assisted by equipment like cameras and office supplies. In this study, both primary and secondary data were gathered through observation, interviews, documentation, and a review of the literature. Data collection, data reduction, data presentation, and conclusion-making are all parts of the data analysis process. The results show that SMP Negeri 7 Padang's approach for dance self-development activities is well-coordinated, adhering to the plans and programs specified by the supervisor. This coordination aligns with the goals of the program and takes into account elements like timing and scheduling. Dance self-development activities have been successfully carried out at SMP Negeri 7 Padang, with students making every effort to stick to the schedule and the allocated location. Nevertheless, there have been issues with insufficient infrastructure and facilities. Every month, notably on Wednesdays from 7:00 AM to 07:40 AM, routine performances presented as part of the dancing self-development activities take place. Students can use these performances as a platform to demonstrate how their exercises have progressed and to build their self-confidence when performing in front of an audience.